Two new species of the genus Poecilagenia Haupt, 1927 from China, with a key to the species (Hymenoptera: Pompilidae). (2nd October 2022) - He, Yi; Ma, Li; Li, Qiang
ABSTRACT: Two new species, Poecilagenia bifasciata He et Ma, sp. nov . and P. fulvipes He et Ma, sp. nov ., are described and illustrated. Two species, P. maruyamai and P. rufithorax are newly reported from China. A key to eight species of the genus Poecilagenia Haupt from China is provided. He, Yi, Li Ma & Qiang Li. In Press. Two new species of the genus Poecilagenia Haupt, 1927 from China, with a key to the species (Hymenoptera: Pompilidae).http://www.zoobank.org/urn:lsid:zoobank.org:pub:20229F2A-D637-42B1-B4CF-97D8C54C5BE4 Poecilagenia bifasciata He et Ma in He, Ma & Li, In Presshttp://www.zoobank.org/urn:lsid:zoobank.org:act:A8B2C837-4E31-484F-B288-913F7C90CA49 Poecilagenia fulvipes He et Ma in He, Ma & Li, In Presshttp://www.zoobank.org/urn:lsid:zoobank.org:act:65989B7A-9821-4562-BE64-52D8A6F47826